2019
DOI: 10.21608/zjar.2019.65093
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF MORINGA LEAVES (Moringa oleifera Lam.) EXTRACT ADDITION ON LUNCHEON MEAT QUALITY

Abstract: The effect of addition moringa leaves extract (MLE) on physical, chemical and sensory properties of luncheon was investigated. Luncheon samples were supplemented with 0.5, 1.0 and 1.5% of MLE. Results showed that supplementation of luncheon with MLE increased its content of protein, fiber and antioxidants. Protein content ranged from 8.49% in control to 10.90% in luncheon sample with 1.5% MLE. Total phenolic content of MLE was ranged from 65 to 67 mg/100g (as Gallic acid equivalent) while, the scavenging effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…Figure 1(e) illustrates the orientation of the surface, as described above. This result is similar to the reports of various authors, namely Chinma andGernah (2007), Hafez Abdel-Samie, andAbdulla (2014), Emelike et al (2015), Mouminah (2015), andEl-Gammal et al (2016). They observed that (2012), the addition of mango flour and powdered moringa leaves significantly decreased…”
Section: Effect On Tastesupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 1(e) illustrates the orientation of the surface, as described above. This result is similar to the reports of various authors, namely Chinma andGernah (2007), Hafez Abdel-Samie, andAbdulla (2014), Emelike et al (2015), Mouminah (2015), andEl-Gammal et al (2016). They observed that (2012), the addition of mango flour and powdered moringa leaves significantly decreased…”
Section: Effect On Tastesupporting
confidence: 90%
“…Figure 1(d) illustrates that flavor acceptability decreases when powdered paragis leaves and mashed bananas increase. A similar trend was observed in cookies (Dachana, 2010;Abdel-Samie & Abdulla, 2014) and bread (Sengev et al, 2013) incorporated with moringa powder.…”
Section: Effect On Flavorsupporting
confidence: 81%
See 1 more Smart Citation
“…In the study conducted by Fapetu et al, the biscuit with a 5% wheat flour substitution for MOLP presented a DPPH inhibition of 40.42%, which is close to the value presented in this study of 35.37% [25]. Although it is not so common to incorporate MOLP extract in biscuits, some authors have tested the inclusion of 1% MOLP extract and also stated that it caused an increase in the antioxidant activity of the biscuits [53].…”
Section: Total Phenolic Content and Antioxidant Capacitysupporting
confidence: 87%
“…Traditionally, the fresh leaves of Moringa are consumed as a snack and integrated into salads and vegetable soups [ 6 , 7 ]. Other promising ways of using the leaves are through the food enrichment and fortification of commonly consumed foods like yoghurt [ 8 ], cake [ 9 ], bread [ 10 ], and biscuits or cookies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%